Assessment of Posteromedial Talus Fractures - C Ramesh Harish (Asian Journal of Medical Research, 2016)
Introduction: To assess cases of posteromedial talus fractures. Subjects and Methods: Sixty- five patients of posteromedial talus fractures of both genders were enrolled. Mechanism of injury, treatment given and complications was also recorded. Results: Out of 65 patients, males were 34 (52.3%) and females were 31 (47.7%). Type of fracture was medial tubercle in 24, postero- medial body fracture in 30 and posterior process in 11 cases. The treatment given was cast in 12, excision in 21 and ORIF in 32 cases. The difference was significant (P< 0.05). Common complications were subtalar arthritis in 4, non- union in 2 and stiffness of ankle joint in 1 case. The difference was significant (P< 0.05). Conclusion: Most common type of fracture was medial tubercle, postero- medial body fracture and posterior process fracture. Common complications were subtalar arthritis, non- union and stiffness of ankle joint.